The Non-Sovereign Self, Responsibility, and Otherness - Kelz, Rosine. author. aut Link
VII, 209 p.
Keywords: Drawing on Hannah Arendt, Judith Butler and Stanley Cavell, this book addresses contemporary theoretical and political debates in a broader comparative perspective and rearticulates the relationship between ethics and politics by highlighting those who are currently excluded from our notions of political community.